2002
DOI: 10.1530/eje.0.1470077
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic tone and obesity: an insight from prolactinomas treated with bromocriptine

Abstract: Objective: It has recently been shown that increased body weight is associated with prolactinomas and that weight loss occurs with normalization of prolactin levels. On the other hand, decreased dopaminergic tone in humans is well correlated with obesity. The objective of this study was to correlate changes in prolactin levels with leptin and body mass index (BMI) in patients with prolactinomas treated with the long-acting dopamine agonist bromocriptine (BC). Methods: Eleven female and twelve male patients, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
139
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 13 publications
(10 reference statements)
6
139
0
6
Order By: Relevance
“…[1][2][3] Subsequent weight loss after treatment with dopamine agonists has also been reported, 3,4 although this has been disputed in one study that showed weight gain after treatment. 5 We therefore undertook a retrospective study of 37 patients with prolactinoma (22 macroprolactinoma and 15 with microprolactinoma, defined by MRI scan of tumour size) and related body weight changes over 24 months to changes in serum and prolactin concentrations.…”
mentioning
confidence: 99%
“…[1][2][3] Subsequent weight loss after treatment with dopamine agonists has also been reported, 3,4 although this has been disputed in one study that showed weight gain after treatment. 5 We therefore undertook a retrospective study of 37 patients with prolactinoma (22 macroprolactinoma and 15 with microprolactinoma, defined by MRI scan of tumour size) and related body weight changes over 24 months to changes in serum and prolactin concentrations.…”
mentioning
confidence: 99%
“…These abnormalities may be alleviated or reversed by dopamine agonists, being the drugs of choice in the treatment of prolactin-secreting tumours and elevated prolactin levels secondary to other disorders [9]. Dopamine agonist-induced normalization of elevated prolactin levels reduced body-weight [7,10] and improved insulin receptor action [4]. The effect of cabergoline on waist circumference, plasma lipids, glycated haemoglobin, insulin and the homeostatic model assessment of insulin resistance (HOMA-IR), despite dose dependency, was observed regardless of the degree of reduction in prolactin levels [11].…”
mentioning
confidence: 99%
“…Notably, abnormalities of the circadian rhythm of prolactin secretion rather than the baseline prolactin level has been associated with weight increase [Doknic et al 2002], which might explain some inconsistencies in the literature mentioned above [Greenman et al 1998;Delgrange et al 1999;dos Santos Silva et al 2011]. As the somatotropin levels were normalized at the point of treatment, we did not substitute this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…However, both standard pharmacological treatments for prolactinoma and cognitive-behavioural treatment often fail to reduce patients' weight [Doknic et al 2002;dos Santos Silva et al 2011]. Overall, there is a considerable need for effective clinical options to address obesity associated with pituitary tumours and to elucidate the relationship between central and peripheral dopamine effects on adipogenesis including the role of prolactin.…”
Section: Introductionmentioning
confidence: 99%